Monooxime-monocarbamoyl Bispyridinium Xylene-Linked Reactivators of Acetylcholinesterase-Synthesis, In vitro and Toxicity Evaluation, and Docking Studies - Musilek, Kamil; Holas, Ondrej; Misik, Jan; Pohanka, Miroslav; Novotny, Ladislav; Dohnal, Vlastimil; Opletalova, Veronika; Kuca, Kamil (ChemMedChem, 2010)
Acetylcholinesterase (AChE) reactivators are crucial antidotes to organophosphate intoxication. A new series of 26 monooxime-monocarbamoyl xylene-linked bispyridinium compounds was prepared and tested in vitro, along with known reactivators (pralidoxime, HI-6, obidoxime, trimedoxime, methoxime, K107, K108 and K203), on a model of tabun- and paraoxon-, methylparaoxon- and DFP-inhibited human erythrocyte AChE. Although their ability to reactivate tabun-inhibited AChE did not exceed that of the previously known compounds, some newly prepared compounds showed promising reactivation of pesticide-inhibited AChE. The acute toxicity of the novel compounds was also determined. Docking studies using tabun-inhibited AChE were performed for three compounds of interest. The structure-activity relationship (SAR) study confirmed the apparent influence of the xylene linkage and carbamoyl moiety on the reactivation ability and toxicity of the agents.
Keywords: pyridinové sloučeniny; oximy; Humans; Pyridinium Compounds; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Erythrocytes; Oximes; Xylenes; Computer Simulation; xyleny; vazebná místa; lidé; zvířata; myši; Binding Sites; Mice; Drug Design; počítačová simulace; Acetylcholinesterase; reaktivátory cholinesterasy; racionální návrh léčiv; erytrocyty; Cholinesterase Reactivators; Animals; karbamáty; Carbamates; acetylcholinesterasa